Women Equity Strive in Society Depicted through Animation Film Characters - Carlo Yannick Leon; Emilia Schmidt (Universitas Ahmad Dahlan, 2021)
The purpose of this research is to identify the female representation depicted in the Disney Renaissance and to investigate why Disney characters struggle to claim their equity as women in their society. The research methods used in this study are classified as qualitative and descriptive. The documentation method and taking notes techniques are used to collect data. The research also employs two method concepts to analyze the collected data, including a gender equity approach analysis and Simone de Beauvoir's second-wave feminism theory. The data consists of linguistic units from various Disney Renaissance stories. The writer discovered three parts in the description of female representations based on data analysis of the female representations depicted in Disney Renaissance: rebel, wise, and adventurous women; confident, intelligent, and repellent of domestication women; and masculine, loyal, and ambitious women. Furthermore, data analysis of Disney characters' struggles in claiming their equality as women in their society reveals that they outperform patriarchal expectations, reject domestication, and practice emancipation by appropriating masculine attributes and roles.